2011
DOI: 10.1007/s10695-011-9518-8
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural indicators of welfare in farmed fish

Abstract: Behaviour represents a reaction to the environment as fish perceive it and is therefore a key element of fish welfare. This review summarises the main findings on how behavioural changes have been used to assess welfare in farmed fish, using both functional and feeling-based approaches. Changes in foraging behaviour, ventilatory activity, aggression, individual and group swimming behaviour, stereotypic and abnormal behaviour have been linked with acute and chronic stressors in aquaculture and can therefore be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
186
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 320 publications
(217 citation statements)
references
References 213 publications
(267 reference statements)
4
186
0
Order By: Relevance
“…ATP stores may be replenished after intense exercise within a 1-h post-exercise recovery period (Carbonara et al 2010), but re-synthesis of glycogen and recovery from lactate accumulation can take twelve hours or more (Marras et al 2013). The proportion of red and white muscle usage reflects physiological state (Lembo et al 2007) and capability to cope with environmental stress Marine and Freshwater Behaviour and Physiology 13 (Martins et al 2012). Whether such changes can be used as an indicator of poor or good welfare is, however, species and context dependent (Herbert & Steffensen 2005).…”
Section: Discussionmentioning
confidence: 99%
“…ATP stores may be replenished after intense exercise within a 1-h post-exercise recovery period (Carbonara et al 2010), but re-synthesis of glycogen and recovery from lactate accumulation can take twelve hours or more (Marras et al 2013). The proportion of red and white muscle usage reflects physiological state (Lembo et al 2007) and capability to cope with environmental stress Marine and Freshwater Behaviour and Physiology 13 (Martins et al 2012). Whether such changes can be used as an indicator of poor or good welfare is, however, species and context dependent (Herbert & Steffensen 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Sánchez et al (2009) observed anticipatory activity of feeding, which could be interpreted as a response to a positive stimulus (see also review by Martins et al 2011), but this was associated with lower plasma cortisol levels than in fish that did not show this behaviour. The multitude of studies describing cortisol elevation in fish relates to stimuli interpreted as negative stressors.…”
Section: Separating Stress From Distressmentioning
confidence: 98%
“…The underlying assumption is that negative feelings in animals will manifest in a stress response, analogous to that which we recognise in humans (Korte 2001;Levine et al 2007). [Please note that behavioural indicators provide an additional potential means of assessing fish feelings (reviewed by Martins et al 2011). Nevertheless, this route may be compromised due to the suggestion that fish, as a common prey item, may not exhibit behavioural changes that could increase vulnerability to predators (CCAC 2005)].…”
Section: Should Fish Welfare Really Address Feelings?mentioning
confidence: 99%
“…In addition, gills are important targets for cortisol in fish (Wendelaar Bonga, 1997). Therefore, opercular movement reflects stress level posed on fish (Martins et al, 2011).…”
Section: Introductionmentioning
confidence: 99%